The Usage of "Turnitin" as an Innovative Educational Tool: Inculcating Critical Thinking in Integrating Naqli and Aqli for Subject of Malaysian Economy - Fuadah Johari; Mohammad Haji Alias; Mohd Firdaus Ibrahim; Asma Abdul Rahman (Elsevier, 2024)
Convenience and ease of ICTs usage in teaching and learning in higher education indeed facilitate and fascinate most of students in the modern world. Thus, this paper focused on the usage of the Turnitin software in the higher education learning (not only for the purpose of anti-plagiarism) but could be used as self-evaluation tool inculcating critical thinking in integrating the Naqli and Aqli in the subject of Malaysian Economy. 271 undergraduate students from the Faculty of Economic and Mumalat, Universiti Sains Islam Malaysia (USIM) taking subjects of Malaysian Economy were involved. A simple individual assignment was instructed early in the semester and were to upload their assignment through the turnitin system in the second week. All students are allowed to review their submission according to their performance in similarity percentage from turnitin system, and are to resubmit their assignment in the tenth week. This paper analyses the relationship between originality, exam grade and gender. At the end of the study, it was found there are significant relation among originality and exam grade as well as gender. Thus, turnitin systems help student in improving their skill in integrating the Naqli and Aqli reasoning for the subject of Malaysian Economy.